CLINICOPATHOLOGICAL EVALUATION OF ABNORMAL UTERINE BLEEDING IN PERIMENOPAUSAL WOMEN - VIVARNA GEDALA; SREE SAILAJA PIDUGU; BALLA SUDHA RANI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Abnormal uterine bleeding (AUB) is defined as any bleeding from the uterus that is deviated from normal in terms of regularity, duration, frequency, and amount of blood loss. It interferes with the woman’s physical, emotional, social, and material quality of life. The prevalence of AUB ranges between 11% and 13% rising to 24% in perimenopausal women. The aim of this study is to analyze the demographic profile and risk factors of AUB in perimenopausal women, to classify the causes of AUB based on PALM-COEIN classification, and to correlate the clinical and sonological findings with post-operative histopathology findings. Methods: A cross-sectional study was conducted in the Department of Obstetrics and Gynecology at GIMSR hospital, Visakhapatnam, for 1 year from September 2022 to September 2023. A total of 151 perimenopausal women with complaints of AUB in the age group of 41–50 years who underwent hysterectomy were included in the study. Results: The most common clinical presentation was heavy menstrual bleeding (HMB) seen in 96 cases (63.5%). Clinically, the PALM component accounted for 61% of cases and the COEIN component accounted for 39% of cases. Ultrasonographically, the PALM component was detected in 76.8% of cases. We calculated the sensitivity, specificity, positive predictive value, and negative predictive value of ultrasound for detection of PALM lesions. Conclusion: Leiomyoma was the most common cause clinically, sonologically, and pathologically. Correlation was good for leiomyoma. USG has good specificity for diagnosis of AUB-A and AUB-P but low sensitivity.